Indoor and outdoor NO2 and SO2 levels in 13 randomly selected preschools from 7 districts in Mpumalanga Province, South Africa - Mudau Rodney; Voyi Kuku; Shirinde Joyce (Wiley, 2024)
Abstract Background Air pollution is a serious worldwide issue, where both outdoor and indoor air quality have a substantial impact on the health of children. Children are more vulnerable to the effects of air pollution due to their developing respiratory systems and higher respiration rates than adults. These children dedicate a substantial amount of time to the preschool setting. The study sought to evaluate the concentration of NO2 and SO2 in both outdoor and indoor environments of preschool facilities. Methods Concurrently, the levels of NO2 and SO2 were measured indoors and outdoors at 13 randomly selected preschools in 7 districts in Mpumalanga Province, South Africa. Radiello passive air samplers were employed to collect gaseous samples. Results The mean levels of NO2 indoors and outdoors were within the recommended criteria outlined by the World Health Organization (WHO), specifically target levels 1-3. Additionally, these values were also below the air quality guides outlined by South Africa, both for yearly and 1‐h mean measurements. Nevertheless, both levels remained above the suitable threshold of 10 µg m−3 outlined by the WHO air quality guidelines. Conclusions It is important to implement proactive measures such as enhancing airflow systems, employing air filters and reducing potential sources of air pollution in preschools, to aid in reducing exposure to indoor and outdoor NO2 and SO2.